Empirical Study on Calculation of Electricity Economic Prosperity Index - A Case Study of H Province. Issue 4 (May 2021) - Di, Haolin; Han, Hongmei
Abstract: According to the theory of economic cycle growth, the method of economic prosperity chronology is used to select the appropriate period of economic prosperity research. Time difference correlation analysis, K-L information quantity and peak valley correspondence method are used to compare the trend value of power consumption in various industries with the trend value of economic data. The indicators that can reflect economic fluctuations are selected and divided into the leading, consistent and lagging indicator groups. The composite index method is used to synthesize the electricity economic prosperity index, including leading index, consistent index and lagging index. Finally, taking H province as an example, an empirical study is carried out to demonstrate the practicability of the model.